Integrated Local Wisdom Values in Strengthening Student Character: Curriculum Design for Madrasah Ibtidaiyah - Kaharuddin Kaharuddin; Hisbullah Hisbullah (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
The purpose of this research is to design a curriculum for a school with a focus on local wisdom. The research method employed in this study is developmental research, utilizing the ADDIE model, which consists of (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The data collection instruments and techniques used in this study include observation, interviews, and questionnaires. The curriculum development design integrates local wisdom values into character enhancement for students at Madrasah Ibtidaiyah, implemented at MI Darul Khaeriyah. This design comprises instructional material in the form of modules, integrating each subject with verses and hadiths. The learning activities are organized using a timetable that allocates time to both general learning activities and those focused on cultural activities such as dance, regional songs, and traditional games. The instructional tools are designed as Lesson Implementation Plans (RPP), in which each step of the learning process is linked to five Luwu cultural values (lempu, ade’le’, getteng, acca, and ininnawa). The assessment design for learning outcomes involves process evaluations conducted during traditional game activities. The results of this study have implications for curriculum development concepts across schools in the Tana Luwu region. By integrating local wisdom values into education, it is possible to reinforce the character development of students.